Pemanfaatan Batang Pinang (Areca catechu Linn) Sebagai Bahan Perekat Likuida Berdasarkan Kedalaman Batang Utilization Of Areca Nut’s Stem (Areca catechu Linn) As The Wood Liquid Material According To Depth Of The Stem - Listi Erawaty Simbolon; Tito Sucipto; Luthfi Hakim (Program studi Kehutanan USU, 2013)
Waste areca nut’s stem (Areca catechu Linn) was one of lignocellulose natural resources potential as raw material of liquid adhesive with through liquifaction method. The part used was the outer stem (L), the middle (T) and the inner (D). The research objective was to determine the quality of adhesive and compared with a standard that was the nature of appearance, degree of acidity (pH), viscosity, density, solids content, gelatin time with SNI 06-4567-1998, free formaldehyde with SNI 06-4565-1998 and ash content with ASTM D 1102-84. Areca nut liquid adhesive made by mixing the powder directly the third part of the areca nut’s stem 20-40 mesh at the temperature 90oC during 2 hours with technical phenol, H2SO4 98%, NaOH 50%, formaldehyde 37%. The results of the research showed that the liquid adhesive stem areca nut partially fulfill the characteristics of phenol formaldehyde adhesives for plywood according to SNI 06-4567-1998. The characteristics that fulfill such as the appearance of the outer stem were dark red and free of dirt, the pH of the three parts of the stem that was 13 (L); 11 (T and D), the density of the outer and the middle was 1.152 (L), 1.173 (T), solids content of the middle part and the inner part was 40% (T and D), the gelatin time of the three part was 332 minutes (L); 315 minutes (T); 305 minutes (D). Free formaldehyde of the three part stem fulfilled SNI 06-4565-1998 was 1.69% (L) 1.30% (T) and 1.24% (D). The liquid adhesive of outer part has characteristics resembling phenol formaldehyde adhesive than the middle and the inner of areca nut’s stem. Key words: waste, stem of areca nut (Areca catechu Linn), liquefaction, wood liquid, adhesives qualities